ELEMENTS OF THE PHILOSOPHY OF HUMAN RIGHTS - Đikanović, Mina R (Glasnik Advokatske komore Vojvodine, 2020)
This paper explores the possibility of the foundation of philosophy of human rights as a distinct philosophical science. Contemporary thematizations of the problem of human rights are being called philosophies, although their essence is not philosophical one. Following Hegel's understanding of modern society and Aristotle's conception of four causes, the author tries to offer an outline for the possibility of foundation of philosophy of human rights as a particular philosophical science. The outline includes observations on subject and method, but also the attempt of concrete application of Aristotle’s four causes on the concept of human rights.
Keywords: philosophy of human rights, human rights, right, law, moral, science, Aristotle, Hegel, four causes